The Effect of Compensation and Promotion on Job Satisfaction with Extrinsic Motivation as an Intervening Variable - Hermanto, Bayu; Agung KJ, I Dewa Gede Agung KJ; Prihono, Ekak; Supriyadi, Supriyadi; Zaharuddin, Zaharuddin (Universitas Ibn Khladun Bogor, 2025)
Compensation and promotion of office are two things that the main purpose of a person working. This study aims to determine the influence of compensation and job promotion on employee job satisfaction with extrinsic motivation as an intervening in PT Rumah Sakit Pelabuhan. The research method used a quantitative approach by distributing questionnaires to 89 samples of employees selected through stratified random sampling technique. Research data was analyzed using Partial Least Squares (PLS) through outer and inner test model. The results showed that the compensation effect on job satisfaction and employee extrinsic motivation. While promotion of office has no effect on job satisfaction but has an effect on employee extrinsic motivation. The extrinsic motivation effect on job satisfaction and become intervening compensation and promotion of position to employee job satisfaction in PT Rumah Sakit Pelabuhan. Job promotion system that is less transparent becomes a matter of concern to the company in order to provide maximum employee satisfaction.